Toms family photograph collection,
Collection of family photographs taken in the Spokane area. Includes one folder of photographs of North Central High School<U+2019>s 1937 band trip to the Apple Blossom Festival in Wenatchee. Includes one folder of scenes taken in and around Spokane from 1928 to 1940. This includes a large photograph of John Toms laying pipe on the west side of Lincoln Street between Main and Trent. Also included is a photograph of Minnie Pearce Kennedy, an evangelist, inside the Masonic Temple in Spokane. The third folder are photographs of lakes in the area. The final folder are group photos of the Spokane County W.C.T.U., the interior of the Philadelphia Pentecostal Church, the 1951 Spokane Indians (baseball team) and employees at Grant<U+2019>s dimestore in downtown Spokane. The two panoramas are graduating classes from North Central High School in 1937 and 1941.